甲府市街地河川水質のpH値等の変動に関する一考察 - 今岡, 正美; 25408; イマオカ, マサハル; Imaoka, Masaharu; 平山, 公明; 25409; ヒラヤマ, キミアキ; Hirayama, Kimiaki; 平山, けい子; 25410; ヒラヤマ, ケイコ; Hirayama, Keiko; et al. (山梨大学工学部, 1995)
Water quality survey of rivers in urban area in Kofu shows a yearly remarkable decrease in BOD and increase in pH at Shorobashi station. Those years high BOD concentration larger than 10mg/1 made the station fall out of the categories in environmental water quality standards, but these years the station falls out of the categories mainly because of high pH larger than 8.5. Since carbonic acid assimilation by aquatic algae seems to be a cause of high pH, investigation of whole day and seasonal variation in water quality was carried out. It can be pointed out that (1) pH keeps slightly alkaline during night and reaches as high as 9 or 10 during daytime, which makes the station out of the environmental water quality standard categories, (2) DO concentration is over-saturated during daytime and reaches around 2mg/1 during night, which means out of the categories, and (3) remarkable variations in pH and DO are observed in summer. River section profiles may amplify the variation at Shorobashi station. departmental bulletin paper